2016
DOI: 10.1002/jssc.201501295
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of molecularly imprinted polymer nanoparticles for the fast and highly selective adsorption of sunset yellow

Abstract: Novel molecularly imprinted polymer nanoparticles were synthesized by precipitation polymerization with sunset yellow as the template and [2-(methacryloyloxy)ethyl] trimethylammonium chloride as the functional monomer. The molecularly imprinted polymer nanoparticles were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, and their specific surface area and thermal stability were measured. The molecularly imprinted polymer nanoparticles had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The adsorption properties of various adsorbent materials for amaranth and sunset yellow in recent years are summarized in Table 1. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Through comparison, it can be found that the adsorption capacity for sunset yellow on PEI/PDMAEMA gel exceeds that of most other adsorbents, while the adsorption capacity for amaranth is signicantly higher than that for other adsorbents. Moreover, the contact time of the adsorbents in this table ranges from 5 minutes to 30 hours; among these, the adsorption time on the PEI/PDMAEMA gel is one hour, which demonstrates that this kind of adsorption method can combine high adsorption efficiency and satisfactory separation speed.…”
Section: Effect Of Adsorption Time On the Adsorption Capacity For Thementioning
confidence: 99%
“…The adsorption properties of various adsorbent materials for amaranth and sunset yellow in recent years are summarized in Table 1. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Through comparison, it can be found that the adsorption capacity for sunset yellow on PEI/PDMAEMA gel exceeds that of most other adsorbents, while the adsorption capacity for amaranth is signicantly higher than that for other adsorbents. Moreover, the contact time of the adsorbents in this table ranges from 5 minutes to 30 hours; among these, the adsorption time on the PEI/PDMAEMA gel is one hour, which demonstrates that this kind of adsorption method can combine high adsorption efficiency and satisfactory separation speed.…”
Section: Effect Of Adsorption Time On the Adsorption Capacity For Thementioning
confidence: 99%
“…They pose a potential risk to the human health, especially if they are excessively consumed. For example, they are nitrous derivatives (azo class) and can be reduced in an organism to an aromatic amine, which is highly unsafe . Accordingly, these food additives fall under the strict legislative control as regards their permitted usage, the enforcement of which necessitates the development of a rapid and robust analytical methodology .…”
Section: Introductionmentioning
confidence: 99%
“…They pose a potential risk to the human health, especially if they are excessively consumed. For example, they are nitrous derivatives (azo class) and can be reduced in an organism to an aromatic amine, which is highly unsafe [3,4]. Accordingly, Abbreviations: EF, enrichment factor; ER%, percent extraction recovery; IEME, in-tube electro-membrane extraction; PP, polypropylene Conflict of interest: The authors declare no conflict of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular imprinting is a powerful technique that is used to produce artificial molecular cavities that are complementary in shape, size, and chemical groups to the targeted molecule. Because of their stability, ease of preparation and specific recognition ability, molecularly imprinted polymers (MIPs) have been successfully used for numerous applications, such as separation, sensors, catalysis, and drug delivery . Moreover, some MIPs for parabens have been reported .…”
Section: Introductionmentioning
confidence: 99%